Comparative Incidence of Inflammatory Bowel Disease in Different Age Groups in the United States. Issue 12 (16th May 2019) - Keyashian, Kian; Dehghan, Melody; Sceats, Lindsay; Kin, Cindy; Limketkai, Berkeley N; Park, K T
Abstract : Data about the incidence of inflammatory bowel disease in the US for patients at the extremes of age are limited. This study showed that, in the commercially-insured and Medicare-enrollee population, the incidence rate in the elderly group in the US is similar to the adult group. Abstract: Background: Data on the incidence of inflammatory bowel disease (IBD) by age group are available in countries outside of the United States or localized populations within the United States. We aimed to estimate the incidence rates (IRs) of IBD by age group using a US multiregional data set. Methods: We used the Optum Research Database to identify incident IBD patients with a disease-free interval of 1.5 years between 2005 and 2015. Overall and age-specific IRs were calculated for 4 different age groups: pediatric (0–17 years), young adult (18–25 years), adult (26–59 years), elderly (>60 years). Time trends of incidence were evaluated in each age group. Perianal phenotype (in Crohn's disease [CD]) was also compared. Results: The mean IR for the cohort (n = 60, 247) from 2005 to 2015 was 37.5/100, 000. The IR was highest in adult and elderly cohorts (36.4 and 36.7/100, 000 respectively). In the adult and elderly groups, the IR for UC was higher than that for CD, whereas the opposite was true in the pediatric and young adult groups. The IR increased over the 10-year study period for all age groups (time trends P < 0.001). The elderly group had less perianal disease than the adult group (20.8 vs 22.3%, respectively; P < 0.05). Conclusions: In one of the most comprehensive evaluations of the incidence of IBD in the United States, we found an incidence rate similar to those of other national populations. We also confirmed differences of specific IBD phenotypes based on age groups, with lower rates of perianal disease in the elderly. Video Abstract: